READINESS OF SMALL AND MEDIUM ENTERPRISES (SMES) TOWARDS A COMPETITIVE HALAL INDUSTRY THROUGH THE IMPLEMENTATION OF HALAL CERTIFICATION - Herianti, Eva; Arifin, Ichwan; Nora, Liza; Marundha, Amor; Rudiatin, Endang; Wahyudi, Slamet; Tanjung, Juita; Muluk, Adrian; Anggraini, Dahlia Tri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The main objective of this community service is to provide some support and guidance to the Small and Medium Enterprises (SMEs) within the Women Farmers Group (KWT) Barokah in Pagedangan Village. Specifically, the assistance aims to facilitate the acquisition of halal certification, which is crucial for enhancing their competitiveness in the global market, given the increasing demand for such certification in the halal industry. It is imperative that forward-thinking SMEs understand the possible commercial advantages linked to halal certification. This program gives SME owners in Pagedangan Village informational materials and advice on the halal certification procedure. The project focuses on the business owners of KWT Barokah, which comprises 22 SMEs a relatively small number in comparison to the overall population of Pagedangan Village. These businesses include sectors such as frozen food, meatball products, catering, flavored milk beverages, herbal drinks, pecel peanut sauce, sukun chips, and Gabin cake filled with tape, among others. The assistance addresses specific issues identified by the community service team and offers tailored solutions to assist these entrepreneurs in obtaining halal certification. The anticipated outcome is that SME owners will enhance the quality of their products through halal certification and improve their readiness to compete in the halal market.